Proceedings of the Conference on Recent Advances in Rock Engineering (RARE 2016) 2016
DOI: 10.2991/rare-16.2016.62
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on rock drillability applied to underground mine development vis-à-vis drill selection

Abstract: Current underground mining scenario is inclining towards mechanized drilling and blasting since it proves advantageous in many ways like controlled excavation profile, limited ground vibrations and better ground control, higher rates of advance, enhanced mine development rates besides maintaining a balance in overall economics of the project. Considering the challenges posed by varied geological conditionsencountered in mining and civil engineering excavations, application of mechanized drilling and blasting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…e uniqueness of the ML is that ML can be able to find the direct and the indirect relationships between the input and the output parameters. To the best of the author's knowledge, there is no direct relationship between the drilling parameters and the in situ stresses; however, as the formation stress increases, the drillability of the formation decreases [17]. [31][32][33][34] showed that rock cuttability decreased in the stressed formations.…”
Section: Data Analysis and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…e uniqueness of the ML is that ML can be able to find the direct and the indirect relationships between the input and the output parameters. To the best of the author's knowledge, there is no direct relationship between the drilling parameters and the in situ stresses; however, as the formation stress increases, the drillability of the formation decreases [17]. [31][32][33][34] showed that rock cuttability decreased in the stressed formations.…”
Section: Data Analysis and Processingmentioning
confidence: 99%
“…en, the set values of these parameters would be adjusted while drilling according to the drillability of the downhole formations which mainly depend on the stress concentration around the wellbore [17,18]. Accordingly, this would be translated into the measured values of SPP, T, and ROP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation